2019
DOI: 10.1093/mnras/stz2879
|View full text |Cite
|
Sign up to set email alerts
|

Hot disk of the Swift J0243.6+6124 revealed by Insight-HXMT

Abstract: We report on analysis of observations of the bright transient X-ray pulsar Swift J0243.6+6124 obtained during its 2017-2018 giant outburst with Insight-HXMT, NuSTAR, and Swift observatories. We focus on the discovery of a sharp state transition of the timing and spectral properties of the source at super-Eddington accretion rates, which we associate with the transition of the accretion disk to a radiation pressure dominated (RPD) state, the first ever directly observed for magnetized neutron star. This transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
60
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 29 publications
15
60
2
2
Order By: Relevance
“…WH18 also observed similar dependence of the pulse profiles on the X-ray luminosity using data from NICER and FERMI -GBM, however, the AstroSat data allowed us to probe into these profiles up to 150 keV using narrow energy bands. Luminosity dependence of the pulse profiles has also been observed in several other X-ray pulsars (see e.g., White et al 1983;Nagase 1989;Doroshenko et al 2020, and references therein).…”
Section: Evolution Of the Pulse Profilesmentioning
confidence: 56%
See 1 more Smart Citation
“…WH18 also observed similar dependence of the pulse profiles on the X-ray luminosity using data from NICER and FERMI -GBM, however, the AstroSat data allowed us to probe into these profiles up to 150 keV using narrow energy bands. Luminosity dependence of the pulse profiles has also been observed in several other X-ray pulsars (see e.g., White et al 1983;Nagase 1989;Doroshenko et al 2020, and references therein).…”
Section: Evolution Of the Pulse Profilesmentioning
confidence: 56%
“…However, based on the spin evolution study of J0243 performed using HXMT data, they also suggested that the NS's magnetic field is ∼ 10 13 G. However, this estimate contrasts with that proposed by Jaisawal et al (2019), whose broad iron line (peaking at 6.67 keV) in NICER spectra requires a dipolar magnetic field in a narrow range between 10 11 G and 10 12 G if it is to originate in the accretion disc. The presence of a weakly magnetized neutron star is also supported by a sharp state transition of the timing and spectral properties of the source at super-Eddington accretion rates (Doroshenko et al 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Recently, however, it was proposed that strong pulsations in ULXs appear in the case of a lucky combination between geometrical parameters of the accreting system (King & Lasota 2020). Another problematic point is related to bright transient X-ray pulsars, which do not show any evidence of beaming at high luminosity states (Tsygankov et al 2017;Doroshenko et al 2020). Additionally, strong beaming in ULXs implies a large number of unbeamed and even diluted sources.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray pulsars, XRPs) has been made over the last years due to extraordinary technical capabilities of the currently operating X-ray observatories. As a result, the range of observable luminosities from such objects extended over nine orders of magnitude from L X ∼ 10 40 − 10 41 erg s −1 for pulsating ultra luminous Xray sources (Bachetti et al 2014;Fürst et al 2016;Israel et al 2017;Rodríguez Castillo et al 2020;Doroshenko et al 2020) to L X ∼ 10 32 − 10 33 erg s −1 for XRPs in quiescent state (see e.g., Campana et al 2002;Doroshenko et al 2014;Wijnands & Degenaar 2016;Tsygankov et al 2017b), allowing to study absolutely different regimes of accretion onto highly magnetized neutron stars (NSs). In addition to the improved technical characteristics, the flexibility in arrange-Corresponding author: A. Lutovinov aal@iki.rssi.ru ment for long-term monitoring campaigns played a major role.…”
Section: Introductionmentioning
confidence: 99%